Double‐shelled nanostructure of SnO2@C tube‐in‐SnO2@C tube boosts lithium‐ion storage - Tian, Qinghua (2021)
In the case of SnO 2 -based lithium-ion battery anodes, the double-shelled hollow nanostructures are expected to possess better performances than their single-shelled counterparts, but the fabrication of double-shelled hollow nanostructures is more difficult than those with single shell because of the increased complexity of structures. Herein, a complex quasi-SnO 2 @C tube-in-SnO 2 @C tube nanocomposite (SnO 2 @C DHNWs) is successfully fabricated by a well-designed facile strategy. The possible formation mechanism of SnO 2 @C DHNWs is also speculated. More importantly, the as-prepared SnO 2 @C DHNWs show outstanding electrochemical performance as a lithium-ion battery anode, that is, 774.5 and 462.5 mAh g −1 are retained at 200 and 1000 mA g −1 after 450 and even 1000 cycles, respectively, demonstrating high capacity, long lifespan, and good rate performances. Thus, excellent performance makes SnO 2 @C DHNWs a promising anode material for advanced lithium-ion batteries. Moreover, it is worth noting that this work may open up a new route to prepare complex nanostructures of SnO 2 @C composites with various morphologies.